Pathways that explain racial differences on edentulism among older adults: 2019 Brazil National Health Survey - Gabriele Rissotto MENEGAZZO; Amanda Ramos da CUNHA; Maria Laura Braccini FAGUNDES; Orlando Luiz do AMARAL JÚNIOR; Jessye Melgarejo do Amaral GIORDANI; Juliana Balbinot HILGERT; Lucas Guimarães ABREU; Fernando Neves HUGO (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract This study aimed to evaluate the pathways that explain the association between race/skin color and edentulism in elderly Brazilians. This was a cross-sectional study using data from participants aged 60 years or older from the 2019 Brazilian National Health Survey, a nationally representative population-based sample. Data were obtained by a structured interview and participants were classified as edentulous if they reported having lost all natural teeth. Information on race, socioeconomic level, behavioral aspects, psychosocial aspects, and access to dental care was collected by interviewers using a questionnaire. The pathways between race/skin color and edentulism were analyzed using structural equation modeling. The final sample of the study included 22,357 participants. Most participants were white (51.5%; 95% confidence interval [CI]: 50.3-52.6), and 36.8% (95%CI: 35.7-37.9) were edentulous. Race/skin color was indirectly associated with edentulism via enabling factors. These findings suggest that socioeconomic inequalities are key in explaining racial inequalities in edentulism among Brazilian older adults.